2008
DOI: 10.1111/j.1600-0560.2007.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry in ocular carcinomas

Abstract: An EMA positive, Ber-EP4 positive immunophenotype supports sebaceous carcinoma, EMA positive, Ber-EP4 negative result supports squamous cell carcinoma and an EMA negative, Ber-EP4 positive result supports basal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 21 publications
6
32
1
1
Order By: Relevance
“…Such studies have had variable results, with some showing high sensitivity and specificity to separate SC from BCC and SCC. [17][18][19][20][21] Our data differs from the previous studies in terms of CK7 expression in both SCC and BCC. We found that 28.5% of BCC, 9% of SCC, and 88.8% of cases of SC expressed CK7.…”
Section: Discussioncontrasting
confidence: 85%
“…Such studies have had variable results, with some showing high sensitivity and specificity to separate SC from BCC and SCC. [17][18][19][20][21] Our data differs from the previous studies in terms of CK7 expression in both SCC and BCC. We found that 28.5% of BCC, 9% of SCC, and 88.8% of cases of SC expressed CK7.…”
Section: Discussioncontrasting
confidence: 85%
“…Variable results have been reported for BER-EP4 and androgen receptor staining in SebCC [10, 11, 15]. The histopathological features and overall immunohistochemical analysis of both of our cases, as demonstrated in Table 1 and Figure 2, were consistent with a diagnosis of SebCC [9-15]. …”
Section: Discussionsupporting
confidence: 63%
“…Adipophilin is expressed in a membranous and vesicular pattern in sebaceous tumors, while a nonspecific granular pattern of staining is found in other tumors such as BCC and SCC [13]. Variable results have been reported for BER-EP4 and androgen receptor staining in SebCC [10, 11, 15]. The histopathological features and overall immunohistochemical analysis of both of our cases, as demonstrated in Table 1 and Figure 2, were consistent with a diagnosis of SebCC [9-15].…”
Section: Discussionmentioning
confidence: 99%
“…8 By immunohistochemistry, the tumor is negative for melanocytic markers (HMB45, MART-1, and S-100) and positive for CAM5.2, Ber-ep4, CK7, EMA, and androgen receptor marker. 23 Diagnosis of this mass was inconclusive by morphology and negative Fontana-Masson. Positive immunohistochemistry staining with MART-1, a melanocyte protein marker along with the demonstration of Type II melanosomes on TEM were used to confirm the diagnosis of metastatic amelanotic melanoma.…”
mentioning
confidence: 99%